Dampak Pandemi Covid - 19 Terhadap Efektivitas Penyelenggaraan Pendidikan Di Indonesia - Zainab Canu (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2022)
The social distancing policy carried out by the government to prevent the transmission of the virus makes learning to be carried out from home by utilizing communication and information technology, or what is known as "online". The online learning media is expected to help the community, especially students, to continue learning in the midst of a pandemic. This study tries to explore the impact of the Covid-19 pandemic on the Effectiveness of Education in Indonesia by using a literature review whose data comes from various literatures, such as books, articles, journals and other research results, which are then analyzed in more depth. This study found positive aspects of online learning where education is not limited by space, students can carry out learning wherever they are. However, the negative aspect of online learning is that not everyone can access online learning media. This is because, in several regions in Indonesia, there are still many who have not been able to utilize communication technology facilities due to lack of mastery of technology, inadequate facilities and infrastructure, and limited costs.